Checklist validation for use in safe heart surgery - Alba Regina Cartaxo Sampaio Thomé; Thaís Honório Lins Bernardo; Patrícia de Albuquerque Sarmento; Jorge Artur Peçanha de Miranda Coelho; Elizabete Melo Montanari Fedocci (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective Build and validate an instrument in checklist format for use in safe cardiac surgery. Method Methodological research carried out in the following stages: literature review; national construction of items and content validation by experts in two stages, at regional level 9 and with 41 judges. For data analysis, the agreement rate per constructed item was determined. Results The construction of version 1 resulted in 49 items, version 2 presented 46 items, and the final version 41 items distributed in Sign in (1 to 27), Time out (28 to 32) and Sign out (33 to 41). All items obtained agreement greater than 80%, considering validated. Conclusion The checklist was built and validated in terms of content, consisting of 41 items, and can be used in the area of cardiac surgery for the implementation of safe care for patients undergoing these procedures.